Inventarisasi Jamur Mikoriza Vesikular Arbuskular dari Rhizosfer Tanah Gambut Tanaman Nanas (Ananas comosus (L.) Merr) - Siti Khotimah, Ratih Nurhandayani, Riza Linda, (Universitas Tanjungpura, 2013)
Vesicular Arbuscular Mycorrhizal (VAM) fungi has an important role to help the growth of pineapple plants (Ananas comosus). The study of inventory of VAM fungi on rhizosphere of pineapple had been conducted for three months from April to July 2013. The research aims to know types of VAM fungi on rhizosphere of pineapple in peat land. Some stages were used in conducting the research that were soil sampling from rhizosphere of A.comosus in Rasau Jaya Umum, isolation and identification of VAM fungal spores, counting number of fungal spores for every 100 gram soil sampling and counting root infection percentage. The research finding showed that VAM fungal spores were Glomus, Acaulospora, and Gigaspora genera. The percentage of pineapple root infected by VAM fungi were in mild level with 33%.